The early impact of COVID-19 on the intellectual and developmental disabilities community in California - Salinas, Giselle; Bolourian, Yasamin; Burt, Beth; Eichelberger, Marcia; Blacher, Jan (Frontiers in Education, 2023)
In this study, we examined how COVID-19 disrupted services for the intellectual and developmental disabilities (IDD) community in California. Secondary data were analyzed from a survey (N=1,082) disseminated by the Autism Society of California in May 2020. Respondents were placed into two categories: autism spectrum disorder (ASD) only (n=794) and IDD other than ASD (n=288). Results revealed significant differences in services between diagnostic groups (<.05). There was a threefold difference in loss of respite services in the ASD (4.3%) versus the IDD group (12.9%); 48.5% in the ASD group reported no change in respite services versus 71.5% in the IDD group. Before the pandemic, a higher mean number of medical and therapeutic services was reported as received in the ASD group (M=1.38) than in the IDD group (M=1.04). However, at the time of the survey, the IDD group reported a higher mean number of such services (M=1.32) than the ASD group (M=1.02). Before lockdown, there were no significant differences in the mean number of services reported by race/ethnicity. However, at the time of the survey, a significantly higher mean number of services was reported by respondents who identified as White (M=1.26) compared to people of color (M=.91), p<.05. When looking at predictors of service access, receipt, and perceived support, age and diagnosis were significant predictors across all. To our knowledge, this study is the first to compare services received by IDD diagnostic groups during COVID-19. Findings help elucidate the negative impact of COVID-19 on the IDD community in California, as well as inform strategies for the ongoing and post-pandemic periods.